THE HISTORICAL MONUMENTS, ANCIENT PLACES, GREAT FIGURES AND MUSEUMS OF THE COUNTRY - Teshaboyeva , Nafisa; Quvvatova , Sevinch (Effective scientific journals, 2025)
Uzbekistan is an ancient country located at the heart of the Great Silk Road, boasting a rich historical heritage. Key historical monuments include Registan Square in Samarkand, the Ark Fortress in Bukhara, and the inner city of Itchan Kala in Khiva. Ancient sites feature Buddhist temples in Termez and Khorezm fortresses. Prominent great figures encompass conquerors and scholars such as Amir Timur (Tamerlane), Ulugh Beg, Al-Khwarizmi, Ibn Sina (Avicenna), Al-Biruni, and poet Alisher Navoi. Notable museums include the Amir Timur Museum in Tashkent, the Savitsky Art Museum in Nukus, and the State Museum of History. This legacy positions Uzbekistan as a treasure of world culture.